GEOTECHNICAL ANALYSIS OF TRANSFORMING A WATER MANAGEMENT STRUCTURE TO A TRANSPORTATION STRUCTURE - Ivan Slávik; Luboš Hruštinec (Acta Polytechnica CTU Proceedings)
This paper analyzes the transformation of the culvert channel under the supply channel of the Gabcíkovo Waterworks into a road tunnel structure and the impact this had on the surrounding rock environment. It presents the engineering-geological conditions in the area, the current structuralmaterial characteristics of the culvert channel and its proposed transformation into a road tunnel. The results of the geotechnical analysis, realized through numeric modelling, are presented as a comparison of deformation changes in the rock environment with respect to changes in loading states corresponding with functional changes in the analyzed culvert.